Einheitlicher Rechtsschutz Europäischer Patente - Carl, Jacob (Mohr Siebeck, 2023)
How to turn a mosaic into a unified whole? The fragmented legal protection of European patents has long been the subject of attempted unification reforms. The Unified Patent Court Agreement has found a way for several national individual property rights to interact together, giving them the same effect as EU-wide property rights.
PublicationDate: 20230208
Keywords: Einheitliches Patentgericht -- Wissenspraktiken -- Oberster Gerichtshof der Vereinigten Staaten -- Einheitspatent -- EPGÜ -- EPG -- personalisierte Preise -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht